PENGARUH KEPEMIMPINAN, MOTIVASI, DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PT TELKOM AKSES SOLO - Nur’Aini, Ochtaviana Ajeng; Saputro, Edy Purwo (Jurnal Manajemen, 2024)
The research topic requires to discover the impact of leadership, motivation, and organizational culture on job satisfaction. This research utilize quantitative methodologies. Accumulation of data along with application of questionnaires, and the responses were scored on a five-point Linkert scale. The data had been examined utilizing the SmartPLS version 3 program. The participants in this research's respondents were employees of PT Telkom Access Solo's SPBU division, who numbered 40 in total. Following a series of analyses, the findings revealed that leadership, motivation, and organizational culture all had a positive and substantial effects on work satisfaction.